The Role of Insurance Agents in Improving Public Understanding of Fire Insurance Products (Case Study at PT Asuransi Askrida Syariah) - Sembiring, Gita Kurnia Sari; Arif Lubis, Fauzi (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
This study discusses the role of agents in increasing public understanding of fire insurance products at PT. Askrida Syariah Insurance. This research uses descriptive qualitative research methods, using primary data obtained through interviews and secondary data from important documents and previous research. The method of data collection is done by interviewing the administrative staff at PT Asuransi Askrida Syariah. Then the author collects some previous research related to the author's research, which is usually called documentation. The method of analysis that the author uses in this research is descriptive, that is, by reducing the data or summarizing important data in the research, displaying the data and concluding the research results. The result of this research is that the method used by the agent at PT. Askrida Syariah in educating the public regarding fire insurance products is by creating events, seminars and promotions from social media. Then the obstacles faced by agents are the lack of public knowledge regarding fire insurance products, and many people think that insurance is not important. The large number of competitors from other insurance companies is also an obstacle in marketing fire insurance products. However, the development of PT Askrida Syariah is very good. It can be seen from 2019 to 2021 that there will be an increase in the number of premiums and also customers.